Rarest variations of ectopic pregnancy: an obstetrician's dilemma - Chaudhari, Kamlesh R.; Sakhalkar, Ashwini; Khyade, Rajeshwari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Ectopic pregnancy is an important cause of morbidity and mortality which has always proven to be a challenge to obstetricians. Increased usage of artificial reproductive techniques has not only increased tubal ectopic pregnancies but also other rarer forms of ectopic pregnancies. With newer diagnostic and therapeutic tools, chance of early detection and intervention has increased many fold. Conservative treatment options have also gained importance. Here we discuss 3 peculiar types of rare ectopic pregnancies-heterotopic pregnancy, caesarean scar ectopic pregnancy and rudimentary horn ectopic pregnancy- and their treatment options.